Factors Associated with Vaginal Discharge among Hormonal Contraceptive Users at Tapa Public Health Center - Madu, Nur Mawaddah; Indah Nurdin, St. Surya; Umar, Siskawati; Zakaria, Fatimah (Jurnal Midwifery, 2025)
Vaginal discharge is often a disturbing complaint for women, especially those using hormonal contraception. Although common, this condition can be concerning, especially if accompanied by changes in color, odor, or itching. This study aims to identify factors associated with vaginal discharge among hormonal contraception users at the Tapa Community Health Center. This study used a quantitative research design with a cross-sectional approach. A sample of 58 respondents was selected using purposive sampling. Data were analyzed using the Chi-Square test.The results showed a relationship between age and vaginal discharge (p-value =0.009 <0.05), occupation and vaginal discharge (p-value = 0.005 <0.05), type of contraception and discharge (p-value = 0.005 <0.05), and vaginal pH and discharge (p-value = 0.000 <0.05). These findings underscore the importance of healthcare professionals providing appropriate education and counseling to hormonal contraceptive users to effectively prevent and manage vaginal discharge.